TREND PENGEMBANGAN MICROGREEN SEBAGAI SISTEM PERTANIAN URBAN DAN PEMASARANNYA - Imas Wildan Rafiqah; Fetty Dwi Rahmayanti (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Microgreen, especially because there is currently a Covid-19 pandemic that has hit almost all countries. Microgreen cultivation techniques are different from other urban farming and are easier to apply so that people are interested in cultivating them. The results showed that 109 respondents who live in urban areas and are familiar with microgreens, 98.2% have an interest in developing microgreens and the remaining 1.8% are not. The reason respondents are interested in microgreen is because it is easy to apply so as to produce quality vegetables that are good for health and microgreens are believed by the respondents to open up new business opportunities. The price offered on this microgreen is much higher than the price of conventional vegetables in general. This can be a potential business with the middle to upper market segment because microgreens are used as food ingredients such as salads or decorations in food in middle to upper class restaurants. In addition, microgreens can also go to supermarkets where the target consumers are consumers who will be aware and ready to be marketed at premium prices.